Total oxidation of dichloromethane and ethanol over ceria–zirconia mixed oxide supported platinum and gold catalysts - Matějová, Lenka; Topka, Pavel; Kaluža, Luděk; Pitkäaho, Satu; Ojala, Satu; Gaálová, Jana; Keiski, Riitta L. (Applied catalysis. B, Environmental, 2013)
•Pt/CeZr and Au/CeZr catalysts tested in dichloromethane and ethanol total oxidation.•Catalytic activity in dichloromethane oxidation: CeZr>Pt/CeZr>Au/CeZr.•Au/CeZr with higher Au loading less active in DCM oxidation due to large Au particles.•Catalytic activity in ethanol oxidation: Pt/CeZr>Au/CeZr>CeZr.•The influence of Pt loading on the mechanism of ethanol oxidation was revealed. Ce0.5Zr0.5O2 prepared by sol–gel method was used as a support for platinum and gold catalysts that were tested in total oxidation of dichloromethane and ethanol. It was shown that the deposition of platinum and gold on Ce0.5Zr0.5O2 support enhanced the reducibility of surface ceria. This phenomenon was more pronounced for platinum catalysts. Introduction of both noble metals led to the decrease of catalysts’ acidity. In total oxidation of dichloromethane, the noble metal catalysts showed lower catalytic performance compared to parent Ce0.5Zr0.5O2, due to lower amount of acid sites that act as chemisorption sites for chlorinated compounds. On the other hand, platinum catalysts exhibited significantly enhanced selectivity to CO2 in comparison with the Ce0.5Zr0.5O2 support. In total oxidation of ethanol, the deposition of platinum on Ce0.5Zr0.5O2 resulted in a significant increase in catalytic performance, while the introduction of gold had only a minor effect. Moreover, the positive effect of higher noble metal loading on catalytic performance was more pronounced for Pt catalysts. For all investigated catalysts, the temperature of the H2-TPR peak corresponding to the reduction of surface ceria correlated with their catalytic performance. The influence of Pt loading on the mechanism of ethanol oxidation was revealed. Based on the concentration profiles of individual by-products/products detected by on-line FTIR analysis, the possible pathways of their formation were suggested. Both noble metal catalysts exhibited higher selectivity to CO2 than the pristine Ce0.5Zr0.5O2.